2017
DOI: 10.1093/toxsci/kfx018
|View full text |Cite
|
Sign up to set email alerts
|

Fasiglifam (TAK-875) alters bile acid homeostasis in rats and dogs: a potential cause of drug induced liver injury

Abstract: Fasiglifam (TAK-875), a Free Fatty Acid Receptor 1 (FFAR1) agonist in development for the treatment of type 2 diabetes, was voluntarily terminated in phase 3 due to adverse liver effects. A mechanistic investigation described in this manuscript focused on the inhibition of bile acid (BA) transporters as a driver of the liver findings. TAK-875 was an in vitro inhibitor of multiple influx (NTCP and OATPs) and efflux (BSEP and MRPs) hepatobiliary BA transporters at micromolar concentrations. Repeat dose studies d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 47 publications
(64 reference statements)
7
51
0
Order By: Relevance
“…But most interestingly, only TAK875‐GlucA 4 became a very potent inhibitor of MRP2, which is very likely a competitive inhibition as a substrate of this transporter. While the inhibitory potential of TAK875 towards most transporters is very similar between three former publications the results regarding MRP2 are contradictory. While Lie et al and Otieno et al describe a potent inhibition, the publication of Wolenski et al describes a simulation of MRP2, a tendency that was also observed by us.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…But most interestingly, only TAK875‐GlucA 4 became a very potent inhibitor of MRP2, which is very likely a competitive inhibition as a substrate of this transporter. While the inhibitory potential of TAK875 towards most transporters is very similar between three former publications the results regarding MRP2 are contradictory. While Lie et al and Otieno et al describe a potent inhibition, the publication of Wolenski et al describes a simulation of MRP2, a tendency that was also observed by us.…”
Section: Resultssupporting
confidence: 61%
“…While the inhibitory potential of TAK875 towards most transporters is very similar between three former publications the results regarding MRP2 are contradictory. While Lie et al and Otieno et al describe a potent inhibition, the publication of Wolenski et al describes a simulation of MRP2, a tendency that was also observed by us. Further scientific analysis of such a striking difference in results is regarded as very meaningful, as inhibition of efflux transporters of the MRP family is highly discussed as a mechanism of hepatotoxicity.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…DILIsym ® modeling has been conducted with other, more potent BSEP inhibitors recently like AMG 009 and TAK‐875 . However, in neither case has elevated total and/or fractionated bile acids been reported in these individual clinical cases of hepatotoxicity due, most likely to lack of clinical samples to examine these effects, even though this phenomenon has been demonstrated in nonclinical species treated with the same drug …”
Section: Discussionmentioning
confidence: 99%